Proverbial factors in translating Tuvan proverbs in the light of normative and poly-lingual paremiography (as contrasted to Russian and English languages) - Bredis, Mikhail A.; Ivanov, Eugene E. (The New Research of Tuva, 2022)
Tuvan proverbs, as it is common for many of Russia’s indigenous peoples, have been mostly translated into Russian language only. This has hindered typological study and lexicographic description of Tuvan proverb corpus beyond the Russian-speaking world. Absence of translation into other languages prevents working on translation methodologies while taking into account various aspects of translation. The most urgent (and most complicated) challenge in this relation lies in studying proverbial factors of translation, which are most crucially important for adequate rendering in target language the ethnically specific nature of Tuvan proverbs.The goal of our study is to define these proverbial factors of vocabulary-based translation and to assess their importance and expression when translating Tuvan proverbs into Russian and English.For empirical material, we turned to published collections of Tuvan proverbs and sayings, sample proverbs recorded in dictionaries and the most authoritative paremiological dictionaries of Russian and English languages.Among the main proverbial factors of vocabulary-based translation (as established in our article) are semantic variability of a proverb, its composition and lexico-grammatical structure, as well as the presence of ethnically and culturally marked notions and tropes. The article also assesses the importance of proverbial factors of translation when these ethnic (linguistic, folklore, or ethnocultural) features are rendered in Russian or English. We examine the ways to solve translation issues and the criteria to select equivalents in foreign languages when Tuvan proverbs are described paremiographically (i.e. when they appear in a multilingual paremiological dictionary).
Keywords: paremiology; paremiography; proverb; translation; Tuvan language; proverbial factor; Tuvan folklore; Russian language; English language